Synthesis and photoluminescence of LiCaBO3: M (M: Pb2+ and Bi3+) phosphor - Pekgozlu, Ilhan; Erdoğmuş, Ertuğrul; Cubuk, Soner; Basak, Ali Sadi; Erdoğmuş, Ertuğrul (Elsevier, 2012)
Pure, Pb2+ and Bi3+ doped LiCaBO3 materials were prepared by a solution combustion synthesis method. The phase of LiCaBO3 were determined using the powder XRD and FTIR. The photoluminescent properties of Pb2+ and Bi3+ doped LiCaBO3 materials were investigated using spectrofluorometer at room temperature. The emission bands of LiCaBO3: Pb2+ and LiCaBO3: Bi3+ were observed at 296 and 378 nm, respectively. LiCaBO3 with different Pb2+ and Bi3+ doping concentrations were analyzed at room temperature. The Stokes shifts of LiCaBO3: Pb2+ and LiCaBO3: Bi3+ were calculated to be 3952 and 6440 cm(-1), respectively. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Inorganic Compounds; Chemical Synthesis; Infrared Spectroscopy; X-Ray Diffraction; Luminescence